AB0761 Prevalence of Enthesitis and Dactylitis, Impact on Disease Severity and Evolution over 12 Months in PSA Patients Treated with Anti-TNF in A Real-World Setting. (10th June 2014) - Rahman, P.; Choquette, D.; Bensen, W.; Khraishi, M.; Shaikh, S.; Arendse, R.; Fortin, I.; Chow, A.; Sholter, D.; Psaradellis, E.; Sampalis, J.S.; Otawa, S.; et al.
Abstract : Background: Spondyloarthritis, including psoriatic arthritis (PsA), is characterized by inflammatory arthritis affecting axial and peripheral joints. It is commonly associated with extra-articular and peri-articular manifestations (PAMs) including dactylitis and enthesitis. Objectives: To evaluate the point prevalence of enthesitis and dactylitis at the time of anti-TNF initiation, their impact on disease severity, and their evolution over time in patients with active PsA treated in a routine clinical practice setting. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for rheumatoid arthritis (RA), ankylosing spondylitis (AS), or PsA with infliximab or golimumab as first biologics or after having been treated with a biologic for <6 months. In this analysis, 132 PsA patients enrolled between 2010 and 2013 were included. The time to no PAM (enthesitis/dactylitis) was assessed with the Kaplan-Meier (KM) estimator of the survival function. Results: At baseline, mean (SD) age and disease duration were 49.1 (10.8) years and 5.8 (7.1) years, respectively. The mean (SD) DAS28 score was 4.0 (1.3). A total of 73 (55.3%) patients had enthesitis and/or dactylitis at baseline; 27 (20.5%) patients had enthesitis, 24 (18.2%) had dactylitis, 22 (16.7%) had both dactylitis and enthesitis, while 59 (44.7%) had none. Significant differences, in disease parameters were observed at baseline based on the presence of a PAM. Specifically, mean (SD) DAS28 was 4.6 (0.8) among patients with enthesitis, 3.9 (1.4) in patients with dactylitis, 4.3 (1.1) in patients with both, and 3.6 (1.4) in patients with none (P=0.023). Similarly, mean (SD) HAQ-DI was 1.5 (0.5), 1.1 (0.8), 1.0 (0.6), and 0.9 (0.6), respectively, in these patient subgroups (P=0.004). A statistical trend was observed for morning stiffness which was 36.7 (34.6), 65.7 (48.1), 54.5 (48.9), and 41.9 (42.3) min in patients with enthesitis, dactylitis, both, and none, respectively (P=0.067). At 6 and 12 months of treatment, 29.1% and 30.4% of patients with available information, respectively, had enthesitis/dactylitis. Treatment with anti-TNF for 12 months resulted in a significant reduction in the prevalence of PAM (P=0.004). Specifically, among patients with enthesitis and/or dactylitis at baseline who had available data at 12 months, 61.1% did not present any manifestation after 12 months of treatment; while 27.3% of patients without enthesitis/dactylitis at baseline developed a new PAM. Survival analysis showed that, for patients with enthesitis/dactylitis at baseline, the KM-based mean time to no PAM was 9.8 months. Conclusions: A high prevalence of enthesitis/dactylitis was observed at anti-TNF treatment initiation (55.3%). Patients with enthesitis, dactylitis or both had increased disease activity compared to patients without a PAM. Treatment with infliximab or golimumab for 12 months was associated with a significant reduction in PAMs with low incidence of new cases. Disclosure of Interest: P. Rahman: None declared, D. Choquette: None declared, W. Bensen: None declared, M. Khraishi: None declared, S. Shaikh: None declared, R. Arendse: None declared, I. Fortin: None declared, A. Chow: None declared, D. Sholter: None declared, E. Psaradellis: None declared, J. Sampalis: None declared, S. Otawa Employee of: Janssen, F. Nantel Employee of: Janssen, A. Lehman Employee of: Janssen, M. Shawi Employee of: Janssen DOI: 10.1136/annrheumdis-2014-eular.2383